International negotiation: a case study implement by Syarikat Air Melaka Berhad / Mardiana Mahadi - Mahadi, Mardiana (Faculty of Business and Management, 2011)
International negotiation is the link between international planning and implementation. The ability to negotiate successfully may very well depend on the efforts being put into preparatory activities, leading to the purpose of this research, to gain a better understanding of pre-negotiation in an international context, by exploring, describing and partly explaining the process. This study is to examine the factors causing the negotiations process implement by the Syarikat Air Melaka Berhad. This study aimed to focus on the factors that will affect the successful of negotiation session in Syarikat Air Melaka Berhad. This study will determine the negotiation process that has been implemented or will be implementing by SAMB to improve their negotiation process. On the other hand, this study will highlight the process that may need some improvement in the negotiation activity in order to achieve 100 percent success in international negotiation. In this study, the researcher collects the information from the interviews, website and secondary data such as journal, article and text book. The collected data are discussed, compared and then finally used to draw general conclusions. After all data has been gathered, it will be interpreted to make it sense for supporting the problems identified. In conclusion, some suggestion and strategies have been made to minimize the problem occur in SAMB. This is important because it will improve negotiation process that happen in SAMB that relate in the international company.